2019
DOI: 10.1007/s12017-019-08575-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of HSPA1B Polymorphisms with Paranoid Schizophrenia in a Polish Population

Abstract: This study aimed to find the potential association between HSPA1B polymorphisms and risk of paranoid schizophrenia, clinical variables of the disease, and suicidal behavior. A total of 901 unrelated Polish subjects of Caucasian origin (377 schizophrenia patients and 524 controls) were recruited. Four single-nucleotide polymorphisms (SNP) were genotyped using PCR-RFLP (rs539689, rs9281590) and TaqMan assays (rs263979, rs6547452). A strong tendency towards statistical significance (p = 0.051) was observed in rs5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…The current study failed to demonstrate any associations between the HSPB1 variants and suicidal behavior in either the entire sample or in the gender-stratified analysis. However, we did find a strong significant association between the HSPA1B rs539689 polymorphism and attempted suicide in patients with SCZ in our previous study [ 30 ]. The C/C genotype and C allele were protective against suicidal behavior in all of the samples as well as in the male and female subgroups.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The current study failed to demonstrate any associations between the HSPB1 variants and suicidal behavior in either the entire sample or in the gender-stratified analysis. However, we did find a strong significant association between the HSPA1B rs539689 polymorphism and attempted suicide in patients with SCZ in our previous study [ 30 ]. The C/C genotype and C allele were protective against suicidal behavior in all of the samples as well as in the male and female subgroups.…”
Section: Discussionmentioning
confidence: 66%
“…Initial analyses with positive findings were performed on a Korean population [ 25 , 26 ]. More recently, the case-control studies performed by our group in a Polish population provided evidence that the HSPA1A (rs1043618) and HSPA1B (rs539689) polymorphisms might be involved in the susceptibility to SCZ in a sex-dependent manner [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the HSPA8 polymorphisms primarily influenced the positive SCZ symptoms (delusions, hallucinations, disorganized speech) in this work. Our previous studies reported a correlation between the HSPA1A (rs1043618) and HSPA1B (rs539689 and rs1061581) polymorphisms and positive symptoms in SCZ patients (Kowalczyk et al 2014(Kowalczyk et al , 2020. Pae et al (2009) also found an association between the HSPA1B rs539689 SNP and PANSS-positive scores at discharge in their experiment investigating the impact of the HSP70 polymorphisms on the clinical symptoms and drug response in schizophrenic patients.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have identified an altered expression of HSPA8 in SCZ patients (Föcking et al 2015;Guan et al 2019). Genetic variations of other HSP70 genes (HSPA1A, -1B, -1L) have also been associated with an increased risk of SCZ and the clinical variables of the disease (Pae et al 2005(Pae et al , 2009Kim et al 2008;Kowalczyk et al 2014Kowalczyk et al , 2018Kowalczyk et al , 2020. One study revealed a difference in the HSPA8 rs1136141 polymorphism between first-episode psychotic schizophrenic patients and healthy participants (Bozidis et al 2014).…”
Section: Introductionmentioning
confidence: 99%